The long-term prognostic value of serum 25(OH)D, albumin, and LL-37 levels in acute respiratory diseases among older adults - Aronen Matti; Viikari Laura; Langen Henriikka; Kohonen Ia; Wuorela Maarit; Vuorinen Tytti; Söderlund-Venermo Maria; Viitanen Matti; Camargo Carlos Arturo Jr; Vahlberg Tero; Jartti Tuomas (BMC, 2022)
Background: Older adults are more susceptible to respiratory tract infection than healthy working age adults. The increased susceptibility of older adults is thought to be interlinked with vitamin D status, nourishment, and immunological state in general. Data are scarce whether these parameters could serve as prognostic markers.
Aim: To study whether serum 25(OH)D, albumin, and LL-37 level could give prognostic value of long-term survival in the older adults with multimorbidity and acute respiratory infection.
Methods: Consecutive episodes of hospital care of patients 65 years and older with respiratory symptoms were prospectively studied as a cohort. Standard clinical questionnaire was filled by the study physician. Laboratory markers included serum levels of 25(OH)D, albumin and LL-37, C-reactive protein (CRP), white blood cell count (WBC) and polymerase chain reaction diagnostics for 14 respiratory viruses. Pneumonia was confirmed by chest radiographs. Respiratory illness severity, death at ward, length of hospital stays, and 5-year survival were used as outcomes.
Results: In total, 289 older adult patients with mean age of 83 years were included in the study. Serum 25(OH)D deficiency (< 50 nmol/liter) was present in 59% and hypoalbuminemia (< 3.5 g/dL) in 55% of the study patients. Low serum albumin level was associated to one, two- and five-year mortality after hospital stay (all P < .05). In addition, it was associated with pneumonia, dyspnea, over 13-night long stay at ward and death at ward (all P < .05). No associations were seen between serum 25(OH)D and LL-37 levels and disease severity, short-term clinical outcome, or long-term survival. Associations between serum 25(OH)D, albumin, and LL-37 levels and respiratory virus presence were not seen.
Conclusions: Serum albumin level on admission seems to give valuable information about the patients' general health and recovery potential in treating older adults with respiratory symptoms. Serum 25(OH)D and LL-37 had no associations with disease severity or long- and short-term prognosis among older adults hospitalized with respiratory symptoms.